Soil Biology Contribution on Agricultural Land Suitability Evaluation of Wet Tropical Megabiodiversity Regions - SUBOWO GITOSUWONDO; EDI SANTOSA; ISWANDI ANAS (Indonesian Center for Agriculture Land Resource Development, 2010)
Indonesia is in the region